History of cardiovascular events and cardiovascular risk factors among patients initiating strontium ranelate for treatment of osteoporosis - Yu J; Tang J; Li Z; Sajjan S; O'Regan C; Modi A; Sazonov V (Dove Medical Press, 2015)
Jingbo Yu,1 Jackson Tang,2 Zhiyi Li,2 Shiva Sajjan,1 Christopher O’Regan,3 Ankita Modi,1 Vasilisa Sazonov11Center for Observational and Real-World Evidence (CORE), Merck & Co., Inc., Kenilworth, NJ, USA; 2Asclepius Analytics Ltd., Wanchai, Hong Kong; 3Merck Sharp & Dohme Corp., Hoddeson, UKPurpose: To estimate the proportion of osteoporosis patients in whom initiating strontium ranelate treatment, under new EMA guidelines, should be contraindicated because of a history of cardiovascular events or risk for cardiovascular events.Materials and methods: This was a retrospective analysis of medical and pharmacy claims using the Clinical Practice Research Datalink database. Patients were included if they had ≥1 prescription of strontium from September 1, 2008 to August 31, 2013, were aged ≥50 as of the index date (the date of the first ever strontium ranelate prescription), and had ≥1 year of medical records pre-index. Cardiovascular events occurring any time pre-index were identified, which included ischemic heart disease, cerebrovascular disease, uncontrolled hypertension, and peripheral arterial disease. Cardiovascular risk factors assessed included 1) diabetes or hypertension any time pre-index; 2) hyperlipidemia in the 12 months pre-index; or 3) obesity in the 12 months pre-index.Results: A total of 7,474 patients were included: 90.4% were women, with an average age of 76.5 years, and 84.5% used osteoporosis therapy, either bisphosphonates or non-bisphosphonates, prior to strontium initiation. A total of 23.6% of patients experienced ≥1 cardiovascular event prior to strontium initiation; the rate was lower among female patients than in male patients (22.4% vs 35.3%, P<0.01). A total of 45.9% had risk factors for cardiovascular events (without cardiovascular event history). Conclusion: More than one-fifth of osteoporosis patients in the UK who used strontium had a cardiovascular event history, and one-half had cardiovascular risk factors prior to strontium initiation.Keywords: osteoporosis, cardiovascular diseases, risk of cardiovascular event, drug therapy, drug safety